ISLAMIC MARKETING STRATEGY IN BUILDING INDONESIA'S HALAL BUSINESS ECOSYSTEM - Harjadi, Dikdik; Kartika, Neng Evi; Gunawan, Wely Hadi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The development of the business industry in Indonesia becomes the most potential market share for other countries. Sharia business is now a lifestyle (lifestyle) of a person in this modern era. The demand for halal and Muslim-friendly (moslem friendly) products is increasing. The importance of a halal business ecosystem to ensure goodness and blessings in consuming products for Muslims needs to be prioritized. This research uses descriptive research methods with quantitative methods. The number of business people in Kuningan regency is 55,486 actors. Samples used in the study as many as 400 business people. The results of this study are variables studied, namely Business Legality, Halal Certification and Labelization on products, and Islamic marketing strategy has a positive influence on the realization of the Indonesian Halal Business Ecosystem, one of which is in Kuningan Regency. Keywords: Legality of Business, Halal Certification and Labelization, Islamic Marketing Strategy, Halal Business Ecosystem.